2022
DOI: 10.1051/0004-6361/202243865
|View full text |Cite
|
Sign up to set email alerts
|

Topological models to infer multiphase interstellar medium properties

Abstract: Context. Spectroscopic observations of high-redshift galaxies slowly reveal the same complexity of the interstellar medium (ISM) as expected from resolved observations in nearby galaxies. While providing, in principle, a wealth of diagnostics concerning galaxy evolution, star formation, or the nature and influence of compact objects, such high-z spectra are often spatially and spectrally unresolved, and inferring reliable diagnostics represents a major obstacle. Bright, nearby, unresolved galaxies observed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…Our findings indicate that ∼75% of the total molecular gas mass is in the warm component, when the fraction of COestimated H 2 mass, M(CO) H 2 , is eliminated from the power-law derived mass estimates, M(>50 K) H 2 . Past studies have shown that the CO-dark gas can account for >70% of the total molecular gas, with the highest percentages found in low metallicity environments (Balashev et al 2017;Madden et al 2020;Lebouteiller & Ramambason 2022;Vizgan et al 2022). Most recently, similar results were reported for the nearby dwarf galaxy WLM (with a metallicity of 13% solar) where Archer et al (2022) find that 90%-100% of the total molecular gas mass is contained in CO-dark H 2 clouds.…”
Section: Importance Of Warm Hsupporting
confidence: 58%
“…Our findings indicate that ∼75% of the total molecular gas mass is in the warm component, when the fraction of COestimated H 2 mass, M(CO) H 2 , is eliminated from the power-law derived mass estimates, M(>50 K) H 2 . Past studies have shown that the CO-dark gas can account for >70% of the total molecular gas, with the highest percentages found in low metallicity environments (Balashev et al 2017;Madden et al 2020;Lebouteiller & Ramambason 2022;Vizgan et al 2022). Most recently, similar results were reported for the nearby dwarf galaxy WLM (with a metallicity of 13% solar) where Archer et al (2022) find that 90%-100% of the total molecular gas mass is contained in CO-dark H 2 clouds.…”
Section: Importance Of Warm Hsupporting
confidence: 58%